Salivary α-amylase response to endotoxin administration in humans - Grigoleit, Jan-Sebastian; Kullmann, Jennifer S.; Oberbeck, Reiner; Schedlowski, Manfred; Engler, Harald (Psychoneuroendocrinology, 2013)
Salivary α-amylase (sAA) is a digestive enzyme that plays also an important role in mucosal immunity. Secretion of the sAA is largely under the control of the autonomic nervous system and increases in sAA activity have repeatedly been observed in response to various stressors. The present study aimed at investigating whether and to what extent sAA activity levels are affected during systemic inflammation. Fourteen healthy male volunteers received intravenous injections of either bacterial endotoxin or placebo at two different occasions in a randomized and double-blinded manner. sAA activity was monitored over a period of 6h together with inflammatory markers, plasma norepinephrine (NE) and salivary cortisol levels, vital parameters, and state anxiety. Endotoxin administration elicited a transient inflammatory response reflected by increases in body temperature, whole blood cell counts, and circulating levels of interleukin (IL)-6. The immune changes were accompanied by a transient increase in sAA activity, elevations in salivary cortisol and plasma NE concentrations, as well as increases in heart rate and state anxiety. Although sAA and plasma NE responses showed distinct time courses, a significant positive correlation over the total observation period was found. Whether the observed sAA response is driven by an increase in sympathetic activity or more generally reflects inflammation induced changes in sympathetic-parasympathetic balance remains to be elucidated.